Acesso à justiça, cortes de despesas e legalidade: uma análise sobre a agregação de comarcas no estado do Rio Grande do Norte - Silva, Rejane Rélbia Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
The state judiciary of Rio Grande do Norte has undergone some changes in recent years. One of the changes, capable of generating negative impacts, was the process of aggregating counties. The beginning of the process of uninstallation of small counties and their aggregation to the other occurred, a priori, under the argument of optimization and redistribution of human resources, based on Resolution No. 184/2013 of the National Council of Justice (CNJ), as well as supply the shortage of magistrates in the counties and rationalize the expenses of the state judiciary. It is well known that the state judiciary, by its very nature, is a guaranteeing institution of rights and cannot violate one of its social functions, namely the access to justice. Given the above, there is a reflection on the possible negative and positive effects arising from the aggregation of counties. Use the approach method and a documentary and bibliographical research technique, using quantitative and qualitative information sources. In the end, it is concluded that the budgetary unavailability of the judiciary that culminated in the aggregation of the counties added an element that made it difficult for the judiciary, the servants and other legal operators to access it through a resolution whose legality is questionable, as well as like, since the delegation for the Court to aggregate counties is unconstitutional, either by the Federal Constitution or by the State Constitution.
Artigo acadêmico
Keywords: Corte de Despesas; Acesso à justiça; Agregação de comarcas; Expense Cut; Access to justice; Aggregation of counties; CIENCIAS SOCIAIS APLICADAS::DIREITO